2022
DOI: 10.1039/d1ra08154c
|View full text |Cite
|
Sign up to set email alerts
|

Potential outstanding physical properties of novel black arsenic phosphorus As0.25P0.75/As0.75P0.25 phases: a first-principles investigation

Abstract: In this study, we design seven stable phases of As0.25P0.75 and As0.75P0.25, focusing on their electrical and thermal properties through first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…And the photocurrent’s sensitivity to changes in the armchair and zigzag directions varies for distinct components, especially the As 0.25 P 0.75 component’s phase being opposite in both directions, which indicates strong polarization anisotropy. This is consistent with our prior findings with electronic changes . As the composition changes, it can be found that the composition mainly affects the magnitude of the response to polarized light with little effect on the phase modulation with polarization angle.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…And the photocurrent’s sensitivity to changes in the armchair and zigzag directions varies for distinct components, especially the As 0.25 P 0.75 component’s phase being opposite in both directions, which indicates strong polarization anisotropy. This is consistent with our prior findings with electronic changes . As the composition changes, it can be found that the composition mainly affects the magnitude of the response to polarized light with little effect on the phase modulation with polarization angle.…”
supporting
confidence: 93%
“…This is consistent with our prior findings with electronic changes. 33 As the composition changes, it can be found that the composition mainly affects the magnitude of the response to polarized light with little effect on the phase modulation with polarization angle. Significantly higher photocurrent for As x P 1−x at x ≥ 0.75.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 The optical properties have been predicted to vary significantly with As/P stoichiometry and distribution, with most configurations of very narrow AsPNRs expecting direct bandgap semiconductors around 0.9 eV, while some configurations provide indirect gaps. 36 Here, AsPNRs have been synthesised by extending the lithium electride PNR synthesis to bAsP, which are incorporated into two devices to demonstrate and measure their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Structure ∆M (meV) ∆V (meV) ∆C(meV) µD (meV) Al/b-Parameters of the GC-FET structures under consideration[39][40][41].…”
mentioning
confidence: 99%